2006
DOI: 10.4103/0253-7613.28208
|View full text |Cite
|
Sign up to set email alerts
|

Role of complex nucleosides in the reversal of oxidative stress and metabolic disorders induced by acute nitrite poisoning

Abstract: Objective: To investigate the possible mechanisms of splenozide influence on oxidative stress and metabolic disorders in tissues caused by acute nitrite intoxication in rats. Materials and Methods: Nitrite poisoning (NaNO 2 , 60 mg/kg, s.c.) was induced in rats pretreated with splenozide (natural metabolite, nucleoside complex; 3 mg/kg, i.p.). The parameters of lipid peroxidation (LPO), antioxidant defense system (superoxide dismutase [SOD], catalase [CAT], glutathione content [GSH], glutathione reductase [GR]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…The control group was given only 0.9% saline at the same volume. The rats were anesthetized and killed by cervical dislocation 50 min after the injection, when methemoglobin formation was at its peak [4]. Blood samples and organs including lung, liver, and kidney were collected for examination of clinical biochemistry.…”
Section: Animals and Study Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The control group was given only 0.9% saline at the same volume. The rats were anesthetized and killed by cervical dislocation 50 min after the injection, when methemoglobin formation was at its peak [4]. Blood samples and organs including lung, liver, and kidney were collected for examination of clinical biochemistry.…”
Section: Animals and Study Designmentioning
confidence: 99%
“…Despite these beneficial effects, supernormal concentrations of nitrites in living organisms cause life-threatening states [4]. Acute nitrite intoxication is manifested primarily by methemoglobin (MetHb) formation (nitrite ion in contact with RBC (red blood cells) oxidizes ferrous iron in hemoglobin to the ferric state, forming stable MetHb which is incapable of oxygen transport) and resultant hypoxia [5], and mice [6] and rats [7,8] exposed to sodium nitrite were shown to achieve elevated concentrations of MetHb in their blood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On other hand, there were significant decrease (p ≤ 0.05), in glutathione reductase , these findings are consistent with (Krishnamoorthy and Sangeetha, 2008) found that LPO level increased due to sodium nitrite administration but vitamin C treatment significantly reduced the lipid peroxidation level and nitrite content (Santos et al, 2009) . Gonchar et al (2006) said that over dose of nitrite caused decrease in glutathione reductase (GR). Vitamin C treated rats showed significant decrease in LPO as compared to sodium nitrite treated group.…”
Section: Disscussionmentioning
confidence: 99%
“…The branched chain amino acids (BCAAs), which include leucine, isoleucine, and valine, are readily metabolized in the muscle (Elwyn 1970), while aromatic amino acids (AAAs), which include phenylalanine and tyrosine are degraded in the liver. The plasma level of this latter group can be an indicator of tissue damage (Gonchar et al 2006). …”
Section: Introductionmentioning
confidence: 99%